P3.261 Global Multilocus Sequence Type (MLST) Analysis of Chlamydia Trachomatis Strains from 16 Countries. (13th July 2013) - Isaksson, J; Bom, R; Saleh, I; Herrmann, B; Bruisten, S
Abstract : Background: The Chlamydia trachomatis MLST database was established in 2007 and is based on five target regions (non-housekeeping genes) and the conventional ompA gene. It enables worldwide epidemiological analyses. Methods: Samples were included from 11 studies focusing on specific risk groups and with different study objectives. Geographical distribution of MLST profiles was carried out and eBURST analysis identified genetic founders. Results: A total of 414 MLST profiles were recognised from 2087 entries. Polymorphism of target regions was reflected in varying numbers of alleles; hctB 89, CT058 51, CT144 30, CT172 41, pbpB 35. With addition of 49 ompA gene variants 459 profiles exist. There were 16 countries from which samples originated, the majority coming from the Netherlands 39%, Sweden 16% and Norway 12%, but also samples from countries in North and South America, Africa and other European countries. Overall 605 (29%) of the database samples originated from men having sex with men (MSM) while the remaining samples were assumed to be from heterosexuals. Singletons or small clusters emerged from 377 of the MLST profiles that were found 1–9 times while 31 profiles were found 10–43 times each. There were 8 profiles that predominated and were each found between 83 and 140 times and constituted large clusters that comprised 868 samples (41.6%). Four of the predominating profiles were strongly associated with MSM, with 96 – 100% of the samples coming from MSM. In the other four large clusters heterosexuals comprised > 90% of the samples. eBURST analysis identified 3 of the 8 predominating profiles as founders, and another 3 as subgroup founders. The genetic diversity was much lower in the MSM clusters compared to clusters in heterosexuals. Conclusions: Worldwide a few C. trachomatis MLST profiles predominate. Different MLST profiles predominate among MSM and heterosexuals.